Microbial interactions and the ecology and evolution of Hawaiian Drosophilidae - O’Connor, Timothy K.; Humphrey, Parris T.; Lapoint, Richard T.; Whiteman, Noah K.; O’Grady, Patrick M. (Frontiers in Microbiology, 2014)
Adaptive radiations are characterized by an increased rate of speciation and expanded range of habitats and ecological niches exploited by those species. The Hawaiian Drosophilidae is a classic adaptive radiation; a single ancestral species colonized Hawaii approximately 25 million years ago and gave rise to two monophyletic lineages, the Hawaiian Drosophila and the genus Scaptomyza. The Hawaiian Drosophila are largely saprophagous and rely on approximately 40 endemic plant families and their associated microbes to complete development. Scaptomyza are even more diverse in host breadth. While many species of Scaptomyza utilize decomposing plant substrates, some species have evolved to become herbivores, parasites on spider egg masses, and exploit microbes on living plant tissue. Understanding the origin of the ecological diversity encompassed by these nearly 700 described species has been a challenge. The central role of microbes in drosophilid ecology suggests bacterial and fungal associates may have played a role in the diversification of the Hawaiian Drosophilidae. Here we synthesize recent ecological and microbial community data from the Hawaiian Drosophilidae to examine the forces that may have led to this adaptive radiation. We propose that the evolutionary success of the Hawaiian Drosophilidae is due to a combination of factors, including adaptation to novel ecological niches facilitated by microbes.